DIGITAL HERITAGE PRESERVATION: THE ROLE OF 3D SCANNING IN DOCUMENTING HISTORICAL ARCHITECTURE IN UZBEKISTAN - Hamidova Mohigul Hayotovna (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Abstract: This study explores how 3D scanning technologies are revolutionizing the documentation and preservation of historical architecture in Uzbekistan. With numerous ancient sites such as those in Samarkand, Bukhara, and Khiva, Uzbekistan is rich in cultural heritage that is increasingly vulnerable to environmental degradation and urban development. The research highlights the role of laser scanning, photogrammetry, and Building Information Modeling (BIM) in preserving architectural integrity while allowing for remote access and educational dissemination. The findings emphasize that digital preservation is not only a tool for conservation but also a bridge between tradition and technology.